Interpretation of the Provisions of International Law Relevant to Baselines - A. N. Vylegzhanin (Московский журнал международного права, 2011)
The article depicts the development of international law applicable to establishment by the coastal state of straight and normal baselines; the contribution to such a development of the ICJ judgment of 1951 on the dispute between Great Britain and Norway and subsequent taking this judgment into account by the UN International Law Commission and the 1-st UN Conference on the Law of the Sea, 1958. A Commentary to the relevant rules of the UN Convention on the Law of the Sea, 1982, is also considered.